Analisis kesalahan siswa dalam menyelesaikan kemampuan pemecahan masalah matematis peserta didik pada materi statistika - Sugeng Sutiarso; Rangga Firdaus; Tasya Safa Melinda (Mandalika Mathematics and Educations Journal, 2026)
Problem-solving ability is a crucial component that students must master to support the character-building process. This ability refers to students' capacity to understand problems by identifying what is known and what is being asked, developing a plan, and verifying the accuracy of the results. This study aims to determine mathematical problem-solving abilities and the types of errors made by students in statistics materials. The method used is library research with a qualitative approach through the analysis of various scientific journals. The results show that students' problem-solving abilities are still low due to the failure to complete all stages of the process. Specific errors found include: students failing to write down known and asked elements because they are confused about the problem's intent, and weaknesses in constructing mathematical models, such as failing to include interval values into formulas. Additionally, incomplete answers were found, such as the failure to create pie charts or bar charts due to a lack of technical understanding and feeling rushed. Students also tend to ignore the re-checking phase, resulting in inaccurate final outcomes. The main causes are a lack of mastery of basic concepts and low student precision.